2006
DOI: 10.1097/01.ta.0000215566.74588.27
|View full text |Cite
|
Sign up to set email alerts
|

Nafamostat Attenuated the Impairment of Fibrinolysis in Animal Sepsis Model by Suppressing the Increase of Plasminogen Activator Inhibitor Type 1

Abstract: Nafamostat appeared to improve impaired fibrinolysis by suppressing the increase of PAI-1 in plasma, though it did not largely improve clinical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Diaz Padilla et al 32 concluded that rat CRP, similarly to human CRP, could activate autologous comlement, supporting that opsonization of ligands with complement is an important biological function of CRP. As has been previously demonstrated in endotoxaemic animal models by several authors 1,3,33,34 , liver damage and loss of organ integrity, with subsequently the increases in plasma AST and ALT levels occur during endotoxemia as a consequence of LPS damage. We determined that LPS significantly increased hepatic enzymes AST and ALT which are markers of hepatic injury.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Diaz Padilla et al 32 concluded that rat CRP, similarly to human CRP, could activate autologous comlement, supporting that opsonization of ligands with complement is an important biological function of CRP. As has been previously demonstrated in endotoxaemic animal models by several authors 1,3,33,34 , liver damage and loss of organ integrity, with subsequently the increases in plasma AST and ALT levels occur during endotoxemia as a consequence of LPS damage. We determined that LPS significantly increased hepatic enzymes AST and ALT which are markers of hepatic injury.…”
Section: Discussionmentioning
confidence: 53%
“…In our work the selected LPS dose (Escherichia Coli, 0.111:B4 1.6 mg/100 g) is a sufficient dose to reach a high concentration of plasma cytokines during endotoxemi in rat 4 . Various researchers have reported the release of LPSinduced proinflammatory cytokines in rat endotoxemic models 3,4,22,23 . Mathiak et al 24 have determined that LPSinduced IL-6 has the highest plasma concentration peak around 4-6 h. Earlier investigation reported that the increase of IL-6 concen-tration correlates with the severity of septic patients 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protease inhibitor is reported to be effective for the endotoxin or lipopolysaccharide‐induced pulmonary vascular injury by inhibiting tumor necrosis factor α production by monocytes 32,33 . Furthermore, protease inhibitor is reported to improve impaired fibrolysis by suppressing the lipopolysaccharide‐induced increase of plasminogen activator inhibitor‐1 in plasma 34 . However, glucocorticoid is reported to increase plasminogen activator inhibitor‐1 expression on vascular endothelial cells and may incline the balance of blood coagulation versus fibrinolysis to coagulation; although pulse steroid treatment reduces serum levels of tumor necrosis factor α 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Furthermore, protease inhibitor is reported to improve impaired fibrolysis by suppressing the lipopolysaccharide-induced increase of plasminogen activator inhibitor-1 in plasma. 34 However, glucocorticoid is reported to increase plasminogen activator inhibitor-1 expression on vascular endothelial cells and may incline the balance of blood coagulation versus fibrinolysis to coagulation; although pulse steroid treatment reduces serum levels of tumor necrosis factor a. 35,36 Protease inhibitor may prevent the progress to multiple organ failure in non-acetaminophen-related fulminant hepatic failure.…”
Section: Figurementioning
confidence: 99%